College and Career Readiness through High School Experiential Learning in the United States - Richard Carroll; Jody Sue Piro (Institute of Business Management, 2020)
This study has explored the perceptions of recent high school graduates in the United States about their levels of preparedness for post-secondary life after they engaged in experiential learning while in high school.  A qualitative, phenomenological methodology was utilized whereby data were collected through a three-level interview protocol applied to a sample of participants (n = 10).  Four of the participants were attending a two-year community college, three were employed in their area of interest, and three were both employed and attending college. Using the analytical procedures of phenomenological reduction, constant comparison analysis was employed whereby ongoing data collection informed recursive data analysis.  As a result of a reductive coding procedure that included open coding, axial code grouping, major thematic identification, and finally, a major finding statement with four themes emerged that included experiential learning as a readiness factor, exposure to college and career experiences, college and career planning, skills and dispositions, and learning.  Implications and recommendations are offered